The association between psychological stress and recurrent aphthous stomatitis among medical and dental student cohorts in an educational setup in India - A Kaleswara Rao; Sudhakar Vundavalli; N R Sirisha; C H Jayasree; G Sindhura; D Radhika (Wolters Kluwer Medknow Publications, 2015)
Introduction: Aphthous stomatitis is very common, affecting about 20-60% of the normal individuals to some degree. Although its etiology is not well-understood, it is multifactorial, and stress could be one possible triggering factor. Aims: The aim was to assess the prevalence of aphthous stomatitis and its association with psychological stress in both medical and dental graduate students. Materials and Methods: A cross-sectional study was conducted in 275 medical and dental student cohorts of an educational setup in India. Data were collected using a self-administered questionnaire, information regarding psychological stress, and 1-year period prevalence of aphthous stomatitis was collected. Data analysis was done with SPSS software version 20 (Chicago Inc., IL, USA). Categorical variables were compared using Chi-square test and comparison between mean stress scores and aphthous stomatitis was done with ANOVA and binary logistic regression was done. P ≤0.05 was considered as statistically significant. Results: The prevalence of aphthous stomatitis in the study population was 78.1% and males were more commonly affected than females. Among the student cohorts, final year MBBS and final year BDS students were highly affected than others, which is statistically significant. Conclusions: Stress increases the risk of aphthous stomatitis. Stress management strategies are necessary for medical and dental graduate students.